The effect of postoperative immobilization in a plaster of Paris back-slab on the surgical wound-healing following the open reduction and plate and screw fixation of the closed calcaneal fractures: a randomised controlled study - Debnath, Anindya; Debnath, Debjita; Rathi, Nitesh; Suba, Santanu; R., Dinesh (International Surgery Journal, 2023)
Background: Intraarticular calcaneal fractures often need open reduction and internal fixation with plate osteosynthesis. Wound complication is one of the common problems encountered following this. It affects the outcome adversely. Our study was done to assess if a postoperative back-slab can offer any significant difference in the incidence of wound complications. Methods: Out of 42 patients with unilateral intraarticular calcaneal fractures, 20 were provided postoperative slab and continued for six weeks. The remaining 22 patients were not provided any plaster. All patients were followed-up for two years. Results: The incidence of wound dehiscence was 2 in the plaster group as well as 8 in the non-plaster group and this was statistically significant (p=0.02). Also, significantly lower heel widening was reported in the plaster group (p=0.03). Although there was no significant difference in the patient-reported outcome (Maryland Foot Score) and the incidence of pain between the two groups, the occurrence of neurological deficit following surgery and the postoperative range of movements were comparable in these two groups. Conclusions: Thus, it may be concluded that postoperative plaster application for the initial six weeks could be a low-cost yet effective way to reduce wound complications following plate osteosynthesis in intraarticular calcaneal fractures.